2018
DOI: 10.1002/jcp.26424
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA TCONS_00041960 enhances osteogenesis and inhibits adipogenesis of rat bone marrow mesenchymal stem cell by targeting miR‐204‐5p and miR‐125a‐3p

Abstract: A growing number of long non‐coding RNAs (lncRNAs) have been found to be involved in diverse biological processes such as cell cycle regulation, embryonic development, and cell differentiation. However, limited knowledge is available concerning the underlying mechanisms of lncRNA functions. In this study, we found down‐regulation of TCONS_00041960 during adipogenic and osteogenic differentiation of glucocorticoid‐treated bone marrow mesenchymal stem cells (BMSCs). Furthermore, up‐regulation of TCONS_00041960 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…To date, many lncRNAs have been demonstrated to regulate osteogenic differentiation, including lncRNA MEG3, lncRNA TCONS_00041960, H19, and so on (B. Li et al, 2017Li et al, , 2018Liao et al, 2017;Shang et al, 2018;Wu et al, 2018;Q. Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…To date, many lncRNAs have been demonstrated to regulate osteogenic differentiation, including lncRNA MEG3, lncRNA TCONS_00041960, H19, and so on (B. Li et al, 2017Li et al, , 2018Liao et al, 2017;Shang et al, 2018;Wu et al, 2018;Q. Wang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the important classes of noncoding RNAs, the role of numerous lncRNAs has been identified in MSCs. For instance, lncRNA TCONS_00041960 [24] can target miR-204-5p and miR-125a-3p to enhance osteogenesis and inhibit adipogenesis. lncRNA-p21 [25], under hypoxic preconditioning, can be a positive factors for MSC migration and survival capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Zhao et al [33] provided evidence that lncRNA-plasmacytoma variant translocation 1 functions as an endogenous 'sponge' by competing for miR-448 binding to regulate expression of the target SERBP1, thereby promoting the proliferation and migration of pancreatic cancer cells. Finally, Shang et al found that lncRNA TCONS_00041960 enhances osteogenesis and inhibits adipogenesis in rat bone marrow mesenchymal stem cells by targeting miR-204-5p and miR-125a-3p [34].…”
Section: Discussionmentioning
confidence: 99%